Global Trends in Patient-Centered Fertility Care: A Bibliometric and Contextual Review - Kushtekova, Aigerim T; Yermukhanova, Lyudmila S; Lokshin, Vyacheslav N; Orakbay, Lyazat Zh; Nurbaky, Ardak N; Nogayeva, Maral G; Sadykova, Gulnar M; Afshar, Alireza (Bangladesh Journal of Medical Science, 2025)
Objective This study provides a comprehensive bibliometric review of patientcentered care (PCC) in in vitro fertilization (IVF), a domain integral to improving patient outcomes, satisfaction, and experiences in assisted reproductive technology. By analyzing global research output and trends, this study aims to identify key themes, contributors, and gaps in the literature to inform future research and practice. Methods Data were collected from Scopus and Web of Science databases, covering the period from 2003 to 2024. Bibliometric analyses, conducted using R Studio and Biblioshiny, examined publication trends, keyword frequencies, and collaborative networks among authors, institutions, and countries. A supplementary literature review contextualized bibliometric findings to address limitations in metadata. Results A total of 54 studies from 33 unique sources were analyzed, revealing an annual growth rate of 11.57% in PCC publications up to 2023. The USA and the Netherlands led in research output, contributing 22 and 16 publications, respectively. Mayo Clinic and prominent authors such as Nelen W. and Kremer J. were key contributors. Keywords like “infertility,” “in vitro fertilization,” and “patient care” demonstrated increasing prominence, underscoring growing interest in PCC. Barriers to PCC were identified at institutional, communication, environmental, and personal levels, while facilitators included multidisciplinary approaches and technological integration. Conclusion This review highlights PCC’s critical role in enhancing IVF outcomes and identifies gaps in psychological support, clinicianpatient communication, and access equity. Recommendations include targeted interventions, international collaborations, and integration of personalized care models. Future research should explore innovative strategies to overcome barriers and advance PCC frameworks in fertility care. BJMS, Vol. 24 No. 04 October’25 Page : 1093-1105